Two wide-bandgap fluorine-substituted benzotriazole based terpolymers for efficient polymer solar cells. (August 2018) - Qi, Feng; Song, Jiali; Xiong, Wentao; Huo, Lijun; Sun, Xiaobo; Sun, Yanming
Abstract: In this work, the fluorine substituted benzotriazole (FBTz) unit is introduced into terpolymers for the first time. FBTz as an acceptor unit was added to the terpolymers of PTT-FBTz and PTTz-FBTz, in which the bithiophene (biTh) unit is used as the donor unit and thieno[3, 2- b ]thiophene (TT) or thiazolo[5, 4- d ]thiazole (TTz) is adopted as a third component, respectively. Compared to PTT-FBTz with TT as the third component, PTTz-FBTz with TTz showed pronounced aggregated shoulder peaks both in solution and film absorption spectra. Electrochemical cyclic voltammetry (CV) shows PTTz-FBTz possesses both lower HOMO/LUMO level than PTT-FBTz due to the higher electronegativity of nitrogen atoms in TTz unit. Subsequently, the bulk-heterojunction polymer solar cells (PSCs) based on PTTz-FBTz show a higher power conversion efficiency of 7.03%, which is much higher than those of PTT-FBTz based devices (PCE = 2.63%). The enhancement of photovoltaic performance based on PTTz-FBTz is mainly attributed to the deeper highest occupied molecular orbital (HOMO) level, higher carrier transport and better molecular packing. Graphical abstract: Highlights: Fluorine substituted benzotriazole (FBTz) unit is firstly introduced to the terpolymers. D1-A1-D1-A2 structure is more efficient strategy in constructing FBTz based photovoltaic terpolymer. PSCs based on PTTz-FBTz shows a high PCE of 7.03% with a high V oc of 0.88 V.